HUBUNGAN FAKTOR REPRODUKSI DENGAN KEJADIAN KANKER PAYUDARA PADA WANITA DI RSUP DR. M. DJAMIL PADANG - Sukmayenti Sukmayenti; Nirmala Sari (Jurnal Riset Hesti Medan, 2018)
Breast cancer is a non-contagious disease, currently a major health problem both in the world and in Indonesia. The incidence of breast cancer is believed to be related to several risk factors. This study aims to determine the relationship of reproductive factors (age of menarche, parity and history of breastfeeding) with the incidence of breast cancer in women. Case control research was carried out at DR. M. Djamil Padang with univariate and bivariate analysis using Chi-square test. Of the 72 samples (36 cases and 36 controls) it was found that respondents with menarche age were 80.6% at risk in the case group and 19.4% in the control group, respondents with risk parity were 33.3% in the case group and 66 , 7% in the control group, respondents with a breastfeeding history were at risk of 65.6% in the case group and 34.4% in the control group. There is a relationship between age of menarche and history of breastfeeding with the incidence of breast cancer. There is no relationship between parity and the incidence of breast cancer. Strengthen health promotion efforts as an effort to prevent breast cancer.Keywords: Reproductive factors, breast cancer